Co-composted Biochar Enhances Growth, Physiological, and Phytostabilization Efficiency of Brassica napus and Reduces Associated Health Risks Under Chromium Stress - Muhammad Naveed (Frontiers Media S.A., 2021)
Among heavy metals, chromium (Cr) contamination is increasing gradually due to the use of untreated industrial effluents for irrigation purposes, thereby posing a severe threat to crop production. This study aimed to evaluate the potential of compost, biochar (BC), and co-composted BC on the growth, physiological, biochemical attributes, and health risks associated with the consumption of Brassica grown on Cr-contaminated soil. Results revealed that Cr stress (Cr-25) significantly reduced the growth and physiological attributes and increased antioxidant enzyme activities in Brassica, but the applied amendments considerably retrieved the negative effects of Cr toxicity through improving the growth and physiology of plants. The maximum increase in plant height (75.3%), root length (151.0%), shoot dry weight (139.4%), root dry weight (158.5%), and photosynthetic rate (151.0%) was noted with the application of co-composted BC under Cr stress (Cr-25) in comparison to the control. The application of co-composted BC significantly reduced antioxidant enzyme activities, such as APX (42.5%), GP (45.1%), CAT (45.4%), GST (47.8%), GR (47.1%), and RG (48.2%), as compared to the control under Cr stress. The same treatment reduced the accumulation of Cr in grain, shoot, and roots of Brassica by 4.12, 2.27, and 2.17 times and enhanced the accumulation in soil by 1.52 times as compared to the control. Moreover, the application of co-composted BC significantly enhanced phytostabilization efficiency and reduced associated health risks with the consumption of Brassica. It is concluded that the application of co-composted BC in Cr-contaminated soil can significantly enhance the growth, physiological, and biochemical attributes of Brassica by reducing its uptake in plants and enhanced phytostabilization efficiency. The tested product may also help in restoring the soils contaminated with Cr.